Optimized Flow Cytometry Strategy for Phenotyping Intramuscular Leukocytes: Application to the Evaluation of Myopathological Processes. Issue 3 (23rd January 2022) - Saidj, Tassadit; Baba Amer, Yasmine; Plonquet, Anne; Henry, Adeline; Souvannanorath, Sarah; Relaix, Frederic; Beldi-Ferchiou, Asma; Authier, François Jérôme
Abstract: Phenotyping intramuscular immune cells is essential for the characterization of dysimmune/inflammatory myopathies (DIM). Flow cytometry (FC) is the most reliable technique for analyzing leukocyte subpopulations and evaluating their activation levels. We developed a purely mechanical protocol for extracting cells from muscle tissue allowing us to preserve cell surface epitopes and determined its applicability to experimental pathology in mice and myopathological diagnosis in human. Skeletal muscle regeneration in mice was associated with a transient enrichment of macrophages (CD11b high Gr-1 + ), myeloid dendritic cells (CD3 − C8 + CD11b high ), CD8 + T cells (CD3 + C8 + ), and NK cells (CD3 − CD11b high NKp46 + ). In murine models of inherited muscle dystrophies, leukocytes represented 23%–84% of intramuscular mononuclear cells, with a percentage of CD8 + T cells (4%–17%) mirroring that of all CD45 + cells, while MDCs remained a minority. In human 16 samples (DIM: n = 9; nonimmune conditions: n = 7), DIM was associated with intramuscular recruitment of CD8 + T cells, but not CD4 + T cells and NK cells. FC allowed concomitant quantification of HLA-DR, CD25, CD38, and CD57 activation/differentiation biomarkers and showed increased activation levels of CD4 + and CD8 + T cells in DIM. In conclusion, FC is an appropriate method for quantifying intramuscular leukocyte subpopulations and analyzing their activation states.